Targeting mutant p53 stabilization for cancer therapy - Wang, Jiajian; Liu, Wenjun; Zhang, Lanqing; Zhang, Jihong (Frontiers in Pharmacology, 2023)
Over 50% cancer bears TP53 mutation, the highly stabilized mutant p53 protein drives the tumorigenesis and progression. Mutation of p53 not only cause loss-of-function (LOF) and dominant-negative effects (NE), but also results in the abnormal stability by the regulation of the ubiquitin-proteasome system and molecular chaperones that promote tumorigenesis through gain-offunction (GOF) effects. The accumulation of mutant p53 is mainly regulated by molecular chaperones, including Hsp40, Hsp70, Hsp90 and other biomolecules such as TRIM21, BAG2 and Stat3. In addition, mutant p53 forms prion-like aggregates or complexes with other protein molecules and result in the accumulation of mutant p53 in tumor cells. Depleting mutant p53 has become one of the strategies to target mutant p53. This review will focus on the mechanism of mutant p53 stabilization and discuss how the strategies to manipulate these interconnected processes for cancer therapy.